Kalimat Majemuk dalam Kumpulan Cerpen Senandung Kunang-Kunang Karya Widiayati - Nurulanningsih, Nurulanningsih; Defita, Defita (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2023)
Abstract This research aims to describe the types of compound sentences and to find out what types of compound sentences are dominant in the short story collection Senandung Kunang-kunang by Widiayati. This research is a descriptive qualitative research. The data collection technique was carried out by means of content analysis techniques (documents) with the intention of finding the meaning of the two clauses that make up the compound sentences in the book collection of short stories Senandung Kunang-kunang by Widiayati. Data analysis techniques using data reduction techniques mean choosing the main thing that becomes the focus of the problem in research or that will be used in this study and discarding those that do not need to be used in research. The technique of checking the validity of the data in this study was assisted by rechecking by the lecturer of the Indonesian Language and Literature Research course. The results showed that in the short story collection Senandung Kunang-kunang by Widiayati there are three types of compound sentences, namely, equivalent compound sentences, multilevel compound sentences, and mixed compound sentences.